Ensino e atuação dos jornalistas na região norte do Brasil e de Portugal - Melo, Gabriela Pereira (2019)
This research expands the debate about the relationship between the university and job´s career, considering the path taken by undergraduates to professional performance and their social actors and understanding the responsibility of those included in this process. The present work aims, in a general way, to know the relation of teaching in journalism with the labor market; understand how the career of journalist corresponds or not to the professional skills required of the graduates in the labor market; to investigate how graduated journalists have adapted to the changes in the world of work in the construction of their professional competences and to understand how the market values or not the academic formation for the development of the professional competences required by the job functions. As an investigative material, the data obtained in a field research are used after a bibliographical and documentary survey in official sites. Interviews were conducted with graduates participants interested in participating. To analyze the interviews and compare the hypotheses, the three steps of content analysis, pre-analysis, material exploration and treatment of results were performed. Authors like Lopes (2013), Pôrto Júnior (2017) and Silva (2018) served as reference for the reflections. It concludes the need for dialogue between academia and the labor market, observing the demands and establishing common issues in Brazil, as done in the second cycle in Portugal. Another issue is that none of the interviewees from Portugal stopped studying in the first cycle, which allows the maturation of professional choices with the support of the university. Another issue pointed out in the state of Tocantins, Brazil, and not even mentioned in Portugal is the university's lack of incentive to entrepreneurship, the autonomous opening of new fields of work. It is understood that this culture of entrepreneurship was not created in the training of the journalist in Brazil and the graduates wait to fit in the market, not to build a new one. Therefore, it is necessary to review the responsibility of the individual and, especially, the contribution of those who form it in this process.